COMBATING FRAUD: HANDCUFFING FRAUD IMPACTS BENEFITS - Johnston, Daniel J. (Assurances, 1997)
The author describes the operations of the Massachusetts lnsurance Fraud Bureau, which began operations in 1991 and recently passed its fifth anniversary. The Fraud Bureau is a public partnership despite being a private entity. lts staff includes people from the insurance industry as well as former law enforcement officials. Ten insurance company executives and five government officials sit on its board of directors. While the process was created by auto insurance companies, after one year workers compensation carriers began making an equal contribution to the Fraud Bureau’s efforts. lts the workers compensation side of the story that is the focus of this article.